New architecture and SCADA for stand‐alone hybrid (medium‐sized asynchronous wind turbine + UPS with battery + photovoltaic array) power system without diesel generator. Issue 7 (1st April 2019) - Choe, Ki Yong; Kim, Ho; Li, Jong U; Hyon, Chung Il; Kang, Il Yong
Abstract: In general, the commercialized medium‐sized asynchronous wind turbines are fully automated facilities designed to operate in parallel connection to the grid; in case of isolated operation, they need to be combined with diesel generator. This paper aims at studying the method of producing electricity of maximal quality with the wind, by constructing a new stand‐alone hybrid (medium‐sized asynchronous wind turbines, UPS with battery, and photovoltaic array) power system without diesel generator. This paper proposes a new architecture of stand‐alone hybrid power system that consists of medium‐sized asynchronous wind turbine, UPS, current limiter (reactor), photovoltaic array, and consumer and dump loads; accordingly, a supervisory control and data acquisition (SCADA) for this system is suggested along with the operation strategies depending on the output power of the UPS and wind turbine, consumer load, and the battery voltage of UPS. The case study was confirmed through the simulation results of the operation of a new stand‐alone hybrid (two 110 kW of asynchronous wind turbines, 250 kVA of UPS with battery, reactor, 36 kW of photovoltaic array, and consumer and dump loads) power system. The results of the simulation showed that the system frequency change of the new stand‐alone hybrid power system was 60 ± 0.5 Hz, and the one of the wind + diesel stand‐alone hybrid system was 60 ± 1 Hz, for the sudden change of consumer load and gust. This new system can be eligible as a standardizing option for the architecture of nondiesel stand‐alone hybrid system and its SCADA system.